Integration of Internet of Things (IoT) in Islamic Religious Education Learning: Implications for Adaptive Curriculum Development and TPACK-Based Learning Management in Higher Education - Titi Hendrawati; Suherman Suherman (Journal of Education and Teacher Training Innovation, 2026)
The implementation of Islamic Religious Education (PAI) in higher education plays a strategic role in shaping students’ character, spirituality, and academic integrity. However, its implementation still faces several challenges, including disparities in teaching practices, limited technology utilization, non-adaptive learning approaches, and non-integrated academic management systems. This study specifically aims to: (1) identify disparities in lecturers’ teaching practices in PAI learning; (2) analyze students’ needs for interactive and adaptive learning environments; (3) examine the limitations of existing academic management systems; and (4) explore how the integration of the Internet of Things (IoT) can address these challenges through adaptive curriculum development and TPACK-based learning management. This research employs a qualitative approach with a phenomenological design conducted at an Islamic higher education institution. The participants consisted of 24 individuals, including lecturers, students, and educational staff selected through purposive sampling based on data saturation principles. Data sources include primary data obtained through in-depth interviews and observations, as well as secondary data from institutional documents. Data collection techniques involved interviews, participatory observation, and documentation, while data analysis used the Colaizzi phenomenological method supported by triangulation and member checking to ensure validity. The findings reveal significant disparities in lecturers’ teaching practices, a strong need for interactive and adaptive learning environments, and limitations in existing academic management systems. The integration of IoT demonstrates considerable potential in enabling real-time data processing, supporting adaptive learning systems, and enhancing data-driven decision-making processes. In conclusion, IoT integration represents a strategic solution for transforming PAI learning into a more adaptive, interactive, and efficient system. However, its successful implementation depends on infrastructure readiness, digital competence, and institutional policy support.